Proceedings of workshop on improved delivery system of diagnosis on animal diseases in Vietnam : (National Institute of Veterinary Research, 2002)
This report suggested that educational efforts for local veterinarians must be conducted continuously to eradication of Toxoplasma infections in Vietnam.